Pengaruh Mind Mapping Melalui Brain Based Learning Terhadap Hasil Belajar Siswa Pada Materi Ikatan Kimia Di Kelas X MIA SMA Negeri 1 Marawola - Purnama, Ririn; Ratman, Ratman; Solfarina, Solfarina (Jurnal Akademika Kimia, 2015)
A research about the influence of mind mapping through brain-based learning in chemical bonding subject on students learning outcomes in class X MIA SMA Negeri 1 Marawola has done. The problem in this research whether there was an influence of mind mapping through brain-based learning to the learning outcomes of students in chemical bonding subject in class X MIA SMA Negeri 1 Marawola. The aim of this study is to determine the influence of mind mapping through brain-based learning in chemical bonding subjecton student learning outcomesin class X MIA SMA Negeri 1 Marawola. This study is a quasi-experiment with purposive sampling. The sample of research consists of two classes, MIA 1, consist of 26 students as a experiment class taught with brain-based learning using mind mapping method and class X MIA 3, consist of 26 students as a control class taugth with brain-based learning using the scientific method. Research results obtained value of x, in the experimental class = 79.30 with a standard deviation = 13.80 and in the control class = 74.30, with a standard deviation = 11.80. From these results, a testing for normality class was done, in the experimental class Ï‡2 value= 4.71 and in the control class Ï‡2 value= 1.85 with the Ï‡2 table = 7.81. The data is normally distributed it as can be seen that both in the experimental class and the controll class Ï‡2 value is less than Ï‡2 table, 4.712.02) in significance level Ï‡ = 0.05 and degrees of freedom dk = 50. It can be concluded that the mind mapping through brain-based learning in these experiment class on chemical bonding subject give a positive effect on student learning outcomes in comparison with the control class SMA Negeri 1 Marawola.